2011
DOI: 10.1016/j.bone.2010.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of bone mineral density in obese premenopausal women

Abstract: Despite being a risk factor for cardiovascular disease and diabetes mellitus, obesity has been thought to protect against osteoporosis. However, recent studies have demonstrated a differential impact of specific fat compartments on bone mineral density (BMD) with visceral adipose tissue (VAT) having potential detrimental effects on BMD. Visceral obesity is also associated with dysregulation of the GH/IGF-1 axis, an important regulator of bone homeostasis. The purpose of our study was to evaluate the differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
123
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 154 publications
(148 citation statements)
references
References 50 publications
(57 reference statements)
11
123
1
8
Order By: Relevance
“…Quantitative computed tomography (QCT) was used to assess body composition and lumbar trabecular BMD. There was an inverse association between BMD and VAT, independent of age and BMI (88). Finally, in unpublished work, Shane and colleagues have shown that trunk fat, as measured by DXA, was inversely related to trabecular bone volume fraction and bone formation rate by histomorphometry (Cohen, 2012 submitted).…”
Section: Bone and Energy Metabolismmentioning
confidence: 95%
See 1 more Smart Citation
“…Quantitative computed tomography (QCT) was used to assess body composition and lumbar trabecular BMD. There was an inverse association between BMD and VAT, independent of age and BMI (88). Finally, in unpublished work, Shane and colleagues have shown that trunk fat, as measured by DXA, was inversely related to trabecular bone volume fraction and bone formation rate by histomorphometry (Cohen, 2012 submitted).…”
Section: Bone and Energy Metabolismmentioning
confidence: 95%
“…In Korean healthy men and women, it was found that visceral fat, measured by computed tomography, was independently and negatively associated with bone mass (87). Aligned with these studies, Bredella et al evaluated in 68 obese (BMI=36.7±4.2 kg·m -2 ) premenopausal women the differential effects of abdominal fat depots and muscle on trabecular BMD of the lumbar spine (88). Quantitative computed tomography (QCT) was used to assess body composition and lumbar trabecular BMD.…”
Section: Bone and Energy Metabolismmentioning
confidence: 99%
“…15 There is a strong correlation between BMD and BMI, and several studies have shown that a decrease in body weight leads to bone loss. 81 A recent meta-analysis investigated the association between BMI and future fracture risk at different skeletal sites and concluded that low BMI remains a risk factor for hip and all osteoporotic fractures. 80 Even when adjusted for BMD, low BMI remains a risk factor for hip fracture.…”
Section: Body Mass Indexmentioning
confidence: 99%
“…New reports, however, show that abdominal obesity may actually be an independent risk factor for bone mass loss and development of osteoporosis [26].…”
Section: Obesitymentioning
confidence: 99%